2004
DOI: 10.1029/2003jb002809
|View full text |Cite
|
Sign up to set email alerts
|

Crustal channel flows: 1. Numerical models with applications to the tectonics of the Himalayan‐Tibetan orogen

Abstract: [1] Plane strain, thermal-mechanical numerical models are used to examine the development of midcrustal channel flows in large hot orogens. In the models, radioactive self-heating reduces the viscosity of tectonically thickened crust and increases its susceptibility to large-scale horizontal flow. Channels can be exhumed and exposed by denudation focused on the high-relief transition between plateau and foreland. We interpret the Himalaya to have evolved in this manner. Channel flows are poorly developed if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
606
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 608 publications
(635 citation statements)
references
References 63 publications
28
606
0
1
Order By: Relevance
“…Although Harrison (2006) thought that there exists insufficient evidence for a channel flow of partially molten crust from beneath the Tibetan Plateau during the formation of the Himalayas, the model of crustal channel flow (Beaumont et al, 2001(Beaumont et al, , 2004) is consistent with many observed features of the Himalayan-Tibetan system. For example, geophysical studies have shown that the partially molten middle crust is being extruded southward below Southern Tibet on the south side of the IYS (Nelson et al, 1996;Unsworth et al, 2005), which demonstrates the existence of crustal channel flow beneath Southern Tibet.…”
Section: Southeastward Ductile Flow Of the Mid-lower Crust Beneath Wementioning
confidence: 59%
See 2 more Smart Citations
“…Although Harrison (2006) thought that there exists insufficient evidence for a channel flow of partially molten crust from beneath the Tibetan Plateau during the formation of the Himalayas, the model of crustal channel flow (Beaumont et al, 2001(Beaumont et al, , 2004) is consistent with many observed features of the Himalayan-Tibetan system. For example, geophysical studies have shown that the partially molten middle crust is being extruded southward below Southern Tibet on the south side of the IYS (Nelson et al, 1996;Unsworth et al, 2005), which demonstrates the existence of crustal channel flow beneath Southern Tibet.…”
Section: Southeastward Ductile Flow Of the Mid-lower Crust Beneath Wementioning
confidence: 59%
“…A model of channel flow in the middle crust has been proposed to explain these phenomena (Beaumont et al, 2001(Beaumont et al, , 2004Hodges, 2006;Hodges et al, 2001;Medvedev and Beaumont, 2006;Nelson et al, 1996;Unsworth et al, 2005). Subsequently, King et al (2007) proposed that the Kuday dykes are the result of partial melting of the Asian plate where it extends south of the IYS as a mid-crustal ductile channel structure beneath Southern Tibet.…”
Section: Southeastward Ductile Flow Of the Mid-lower Crust Beneath Wementioning
confidence: 99%
See 1 more Smart Citation
“…These geological constraints were subsequently simulated in the numerical models of Beaumont et al (2001Beaumont et al ( , 2004. In this model, partial melting occurs only in the middle crust beneath the seismogenic upper crust, but not in the lower crust, which is underthrust Indian Shield Precambrian granulites (Caldwell et al 2009).…”
Section: Himalayan Channel Flow Modelsmentioning
confidence: 99%
“…Clark & Royden 2000;Haines et al 2003) and (b) the Himalayan mid-crustal 'channel flow' model (e.g. Beaumont et al 2001Beaumont et al , 2004Grujic et al 2002;Searle et al 2003Searle et al , 2006Searle et al , 2010bLaw et al 2004Godin et al 2006).…”
mentioning
confidence: 99%